2014
DOI: 10.1021/ma501516s
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Polymerization Based on Carbene Polycyclopropanation

Abstract: International audienceThe first polymerization exploiting the carbenic reactivity of homogeneous gold catalysis has been devised. In the presence of a gold catalyst, monomers incorporating both a propargylic ester and an alkene moiety polymerized through a metallocarbene generation/cyclopropanation sequence to afford the corresponding macromolecules. This approach constitutes an unprecedented example of cyclopropanation-based polymerization and allows access to original macro-molecule skeletons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“… [20–22] Significant advancements in catalyst and methodology development have resulted in improved yields, turn‐over frequencies (TOF), and functionality tolerance, enabling the synthesis of structurally diverse and complex organic molecules. Access to new macromolecular chemistries could be obtained directly from aryl‐containing building blocks and various alkyne comonomers if an analogous polymerization chemistry was developed; however, the use of Au as a polymerization catalyst remains essentially unexplored [23–27] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… [20–22] Significant advancements in catalyst and methodology development have resulted in improved yields, turn‐over frequencies (TOF), and functionality tolerance, enabling the synthesis of structurally diverse and complex organic molecules. Access to new macromolecular chemistries could be obtained directly from aryl‐containing building blocks and various alkyne comonomers if an analogous polymerization chemistry was developed; however, the use of Au as a polymerization catalyst remains essentially unexplored [23–27] …”
Section: Methodsmentioning
confidence: 99%
“…Access to new macromolecular chemistries could be obtained directly from aryl-containing building blocks and various alkyne comonomers if an analogous polymerization chemistry was developed; however, the use of Au as a polymerization catalyst remains essentially unexplored. [23][24][25][26][27] This motivated our investigation of Au as a polymerization catalyst, in which we envisioned sequential intermolecular hydroarylation reactions (polyhydroarylations) could occur between bifunctional comonomers containing aromatic C(sp 2 ) À H and C C bonds (Scheme 1 B). We evaluated the model reaction between 1,2,4,5-tetramethylbenzene (1) and 1,4-diethynylbenzene (2) toward poly[(tetramethyl-1,4-phenylene)ethene-1,1-diyl-1,4-phenyleneethene-1,1-diyl] (P1, Table 1).…”
mentioning
confidence: 99%
“…33 Notably, we developed a new polymerization process by polycyclopropanations 34 of styryl propargyl acetates. 35 In collaboration with the Ryu's group in Osaka, we also considered the possibility to incorporate CO into the Rautenstrauch rearrangement. In the first case, 1,3-O-acyl migration, as we will also see later, leads to rhodacyclopentenes E, which insert CO to give 19.…”
Section: Scheme 4 Total Synthesis Of Sabina Ketonementioning
confidence: 99%
“…33 Notably, we developed a new polymerization process by polycyclopropanations 34 of styryl propargyl acetates. 35 In collaboration with the Ryu's and Fukuyama's group in Osaka, we also considered the possibility to incorporate CO into the Rautenstrauch rearrangement. 36 While the platinum and gold carbene intermediate complexes D could not trap CO, rhodium(I) catalysis proved to be the right option.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…A polymer chain reaction was reported where chain growth is due to intermolecular cyclopropanation using a carboxylate shift-generated carbene complex (e.g. 1318) [1212]. A computational study was reported for selectafluor-mediated gold-catalyzed oxidative bond forming reactions of propargylic carboxylates [1213].…”
Section: Scheme 101 Formation Of Ring-fused Cyclopropanes Using Metamentioning
confidence: 99%